2021
DOI: 10.1242/jcs.259340
|View full text |Cite
|
Sign up to set email alerts
|

A cytosolic reductase pathway is required for efficient N-glycosylation of an STT3B-dependent acceptor site

Abstract: N-linked glycosylation of proteins entering the secretory pathway is an essential modification required for protein stability and function. Previously, it has been shown that there is a temporal relationship between protein folding and glycosylation, which influences the occupancy of specific glycosylation sites. Here, we used an in vitro translation system that reproduces the initial stages of secretory protein translocation, folding and glycosylation under defined redox conditions. We found that the efficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The interference of disulfide bonds with N-glycosylation of VEGF 121 are in line with the structural studies showing the inaccessibility of the catalytic site of the bacterial OST homolog to the folded protein domains and with previous work demonstrating that cytosolic reducing poise improves STT3B activity [ 10 , 36 ]. The unanticipated finding of the current study is that the less oxidizing ER redox poise caused by ERO1 loss, while allowing the secretion of correctly assembled disulphide bonds in VEGF 121 , nevertheless alters their N-glycosylation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The interference of disulfide bonds with N-glycosylation of VEGF 121 are in line with the structural studies showing the inaccessibility of the catalytic site of the bacterial OST homolog to the folded protein domains and with previous work demonstrating that cytosolic reducing poise improves STT3B activity [ 10 , 36 ]. The unanticipated finding of the current study is that the less oxidizing ER redox poise caused by ERO1 loss, while allowing the secretion of correctly assembled disulphide bonds in VEGF 121 , nevertheless alters their N-glycosylation.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, MAGT1 and TUSC3, which are both transmembrane proteins, share a lumenally-localized thioredoxin-like motif (CXXC) [ 9 ]: mutagenesis of this motif reduces glycosylation of STT3B substrates. Furthermore, N-glycosylation of both STT3A and STT3B substrates is favored by reducing conditions, suggesting a causal link between a more reduced ER redox poise and improved N-glycosylation [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, this link might be conveyed by any output of mitochondrial activity, and, indeed, recent work suggests that exchange of calcium, reactive oxygen species (ROS), and potentially other metabolites between mitochondria and the ER likely influences metabolic disease progression ( Arruda et al, 2014 ; Tubbs et al, 2014 ; Theurey et al, 2016 ; Theurey and Rieusset, 2017 ; Tubbs et al, 2018 ). However, cellular redox—more specifically the linkage of nutrient oxidation to NADPH production—is emerging as an additional potential candidate for transmitting nutrient signals to the ER ( Gansemer et al, 2020 ; Van Lith et al, 2021 ).…”
Section: The Endoplasmic Reticulum and Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…For example, cytosolic NADPH plays a role in reduction of non-native disulfides that form in the ER ( Poet et al, 2017 ). NADPH is also implicated in regulating N-linked glycosylation efficiency, since both the ER glycosylation machinery and the proteins being glycosylated are redox sensitive ( Van Lith et al, 2021 ). Similarly, we recently showed that NADPH generated by the TCA cycle leads to a hypo-oxidizing ER and, surprisingly, increased sensitivity to ER stress ( Gansemer et al, 2020 ).…”
Section: Pathways Linking Reduced Nicotinamide Adenine Dinucleotide P...mentioning
confidence: 99%
See 1 more Smart Citation